S82. 7T MR SPECTROSCOPY ACROSS PSYCHOTIC ILLNESSES AND BIOLOGICAL RELATIVES. (9th April 2019) - Demro, Caroline; Schallmo, Michael-Paul; Marjanska, Malgorzata; Sponheim, Scott
Abstract: Background: Psychotic disorders, including schizophrenia and bipolar disorder with psychotic features, can be conceptualized in a dimensional rather than categorical way. Such disorders might share similarities in illness pathophysiology. Disruptions in certain neurotransmitter systems (aberrant dopamine; hypo-functioning glutamatergic NMDA receptors) are thought to be involved in the development of psychosis. Whether such neurotransmitters fluctuate in tandem with psychotic symptom severity remains unclear. We sought to examine dimensional symptom severity of psychosis in relation to neurochemical concentrations using magnetic resonance spectroscopy, which allows for the quantification of neurochemicals. Methods: As part of the ongoing Psychosis Human Connectome Project, we acquired MR spectroscopy data at 7 Tesla, which has better spectral resolution in general than data acquired at lower field-strengths. Using a STEAM sequence, we measured both excitatory (glutamate) and inhibitory metabolites (Gamma-Aminobutyric Acid; GABA) in the prefrontal cortex among individuals with psychosis (n=18) and healthy control participants (n=12). In order to explore potential genetic liability, we also studied first-degree biological relatives of individuals with a psychotic disorder (n=8). Results: Among individuals with psychosis, we found a significant inverse correlation between glutamate and disorientation as measured by the Brief Psychiatric Rating Scale (BPRS; r = -.61, p = .004). Among the full sample with good-quality imaging data (N=30), we found a significant positive correlation between GABA and cognitive-perceptual disturbances as measured by the Schizotypal Personality Questionnaire (SPQ; r = .40, p = .030). Discussion: More severe psychotic-like symptoms corresponded with lower concentrations of the excitatory neurotransmitter glutamate and higher concentrations of inhibitory GABA. These findings suggest that an imbalance in excitatory and inhibitory neurotransmitters may underlie psychotic-like symptoms that are present in a range of clinical and non-clinical populations. As we continue to collect data, we will increase our sample size which will enable us to examine whether concentrations of these metabolites differ across individuals affected by psychotic illness, those carrying genetic liability for such disorders, and non-psychiatric control participants.